APPLYING THE USES AND GRATIFICATIONS THEORY TO DECODE NIGERIAN UNIVERSITY STUDENTS’ ELECTRONIC DISCOURSE - Iyere, Theodore (Top Linguistic and Language Journal (TLLJ), 2025)
This paper applies the Blumler and Katz’s Uses and Gratifications Theory to decode Nigerian university students’ electronic discourse, which comprises peculiar spelling forms generated by the students in their various social media chats. Suffice it to say that the Shorthand form of typing or writing had been in existence in the past, but the advent of social media further escalated it to an unimaginable creative degree this time. Unlike the old form of shorthand where symbols have generally agreed usage, social media gives its users the freedom to express orthographic idiolect and idiosyncrasies. It is this freedom that results in the different spelling variants of the same word that social media subscribers have introduced to the platforms: a phenomenon that has caught the interest of linguists and researchers. All forms of writing in social media are termed Electronic Discourse (Electronic Language or e-Language). Crystal in his book Language and the Internet gave other words used in place of e-language as Netspeak, Netlish, Weblish, Internet Language, Cyberspeak, Electronic Discourse, Interactive Written Discourse, and so on (28). The researcher, over a period of three months, and using a corpus-based approach encapsulated in the simple random sampling technique, collated data from 100 students (ages 18 – 30) registered in two public universities located in the Federal Capital Territory (FCT) Abuja. The researcher generated two chats from any of the social media platforms that the respondents voluntarily presented to him. The data collated was analyzed using simple percentage and frequency analyses that presented information using relevant tables to guide the analysis. The researcher further used qualitative analysis grounded in uses and gratifications theory to determine the motivations underlying students’ use of peculiar spelling forms in their electronic discourse. Five categories consistent with Uses and Gratifications Theory emerged from this analysis, indicating that the students regularly used peculiar spelling forms for 1) entertainment, 2) convenience, 3) increasing social interaction, 4) seeking and sharing coded information, and 5) deliberately trying to restrict other people from comprehending the peculiarity of the language being selected. The study further found that English words and expressions used by many Nigerian university students in their e-language (social media chats) differed graphologically and morphologically from conventional ones. Interestingly, the omission of letters, unpopular academic abbreviations and acronyms, and the various spellings used by the students on their respective social media platforms did not constitute language or communication problems to them. Consequently, it would be of great benefit for language scholars to devise a way to accommodate these special language usages, which have become inevitable in the present dispensation due to the rapid nature of technological advancement in the world.